Family ‘Three-folding’: a conciliatory and affirmative paradigm for human development in caring consciousness in society. - Siwella, Vimbainashe (Stellenbosch : Stellenbosch University, 2011)
Thesis (MTh)--Stellenbosch University, 2011.